24 JANUARY DECISION IN TURKEY STARTED WITH TODAY'S ECONOMIC AND FINANCIAL STRUCTURE FINANCIAL LIBERALIZATION REFLECTIONS - Selçuk BAYRAMOĞLU (Fırat University, 2019)
Starting in the year 1940 and is the often talked about the globalization of today's self-needed economic policies both in the political structure of the main agenda in the 1980s. Social and economic components that make up the world economy, with each other and / or expressed in the articulation with the world market globalization, the disappearance of the economic aspects of the financial markets that separates the border and speed to win the international capital flows (liberation) is the process. Will give a definition literally happen if financial liberalization, the state should monetary and fiscal policy instruments with both other different print elements with the restrictions that hinder the spontaneous functioning of the financial system and / or the elimination of intervention and thus can be expressed as to ensure the functioning of the financial market mechanisms. Financial liberalisation programme took its theoric basis from neo-liberal policies. Financial liberalisation programme which gaining acceleration at the end of 1970s came Turkey’s agenda with decisions of 24 january 1980. Liberalisation was widely completed in three step in our country. First of them was liberalisation of goods and service trade, second one was domestic financial liberalisation that was provided with the removing restrictions on interest rates, third and last one was foreign financial liberalisation that was completed with removing restrictions on capital movement. The aim of this study, is to evaluate the results of the decision of 24 January 1980 which is the first step in financial liberalization. Furthermore, is to evaluate what kinds of innovations brought to todays economic and financial structure, financial